Islamic Education in the Aceh Sultanate Period - Muhammad Habibi Azimi; Abd Mukti; Sapri Sapri (Edumaspul: Jurnal Pendidikan, 2024)
This scientific study aims to examine more deeply Islamic education during the Aceh Sultanate. This scientific study uses qualitative research methods with the type of library research. The data used in this study is secondary data, including accredited journals and books that are appropriate to the topic studied. The results of the analysis state that the Aceh Sultanate was the result of the amalgamation of Islamic kingdoms in the Aceh region around the 16th century AD, which experienced prosperity during the reign of Sultan Iskandar Muda. What underlies the progress of the Acehnese Sultanate is Islamic law as the state ideology, being the center of study, intellectualism, and producing various Islamic literature. Therefore, Islamic education has become the main spearhead in the progress of the Sultanate of Aceh, to the point where it has the title Center for Islamic Studies.